The Second Karabakh War: Turkey's South Caucasus Policy and Iran's Strategic Interests - Mohammad Afrasiyab (Banber Arevelagitut'yan Instituti)
Turkey, through its neo-Ottomanism policy, has framed the South Caucasus as part of its ethnic and identity sphere, deepening political, economic, and security ties with Azerbaijan under the slogan “one nation, two states.” The security paradigm shift triggered by the 2020 Karabakh conflict between Azerbaijan and Armenia allowed Ankara to redefine its operational environment in the South Caucasus, transforming itself into a key regional actor. Turkey’s assertive engagement during the Second Karabakh War and its unequivocal support for Baku have posed significant challenges to the Islamic Republic of Iran’s national interests in the region. This study addresses the following question: What are the dimensions of Turkey’s foreign policy approach in the South Caucasus following the Second Karabakh War, and how will it impact Iran’s geopolitical and geocultural interests in the region? The hypothesis posits that Turkey’s post-war foreign policy—anchored in the Ankara-Baku strategic alliance and driven by ethnic-identity narratives, economic-military integration, and geopolitical ambitions—will undermine Iran’s security, geopolitical, and economic interests in the South Caucasus. Focusing on the period from 2020 to 2023, this research examines Turkey’s regional strategy after the Second Karabakh War, analyzing its implications for Iran’s strategic positioning.